Technologies for electrical power conversion, efficiency, and distribution methods and processes - Antchev, Mihail Hristov, 1955- (Engineering Science Reference, 2010)
"This book presents an overall description of electrical energy conversion technologies and required power electronic converters"--Provided by publisher.
"Premier reference source"--Cover.
Keywords: Electric power.; Energy conversion.; Electric power production.; elektronické knihy; electronic books